2014
DOI: 10.1371/journal.pone.0108674
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and Risk Factors to Coxiella burnetii, Spotted Fever Group and Typhus Group Rickettsiae, and Bartonella henselae among Volunteer Blood Donors in Namibia

Abstract: BackgroundThe role of pathogen-mediated febrile illness in sub-Saharan Africa is receiving more attention, especially in Southern Africa where four countries (including Namibia) are actively working to eliminate malaria. With a high concentration of livestock and high rates of companion animal ownership, the influence of zoonotic bacterial diseases as causes of febrile illness in Namibia remains unknown.Methodology/Principal FindingsThe aim of the study was to evaluate exposure to Coxiella burnetii, spotted fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 58 publications
1
32
0
2
Order By: Relevance
“…Q fever seroprevalence rates in humans varied from 1% in Chad (52) to 16% in Egypt (53). More recently, a seroprevalence study among blood donors in Namibia identified a 26% seropositivity rate (54). In an agropastoral region of Algeria, seroprevalence rates of 15%, with peaks up to 30% in villages where the disease is hyperendemic, have been observed (55).…”
Section: The Different Epidemiological Profilesmentioning
confidence: 99%
“…Q fever seroprevalence rates in humans varied from 1% in Chad (52) to 16% in Egypt (53). More recently, a seroprevalence study among blood donors in Namibia identified a 26% seropositivity rate (54). In an agropastoral region of Algeria, seroprevalence rates of 15%, with peaks up to 30% in villages where the disease is hyperendemic, have been observed (55).…”
Section: The Different Epidemiological Profilesmentioning
confidence: 99%
“…The presence of SFG rickettsiae species has not yet been reported in Namibian dogs and cats; however, serological evidence has been reported in human populations (Noden & Van der Colf 2013 ; Noden et al . 2014b ). While the main tick reservoir or vector species in Africa for R. conorii and R. africae is probably R. sanguineus (Walker et al .…”
Section: Tick-borne Pathogens Of Companion Dogs and Catsmentioning
confidence: 99%
“… 1998 ) and Namibia (Noden et al . 2014b ). Vectored by the cat flea, C. felis , or the rat flea, X. cheopis (Laudisoit et al .…”
Section: Flea-borne Pathogens Of Companion Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports continue to demonstrate that these tick- and flea-borne pathogens are impacting human and animal populations in low resource countries which lack technical and material capabilities. Often, these countries are not aware that these pathogens are circulating in their populations [ 1 , 3 , 7 , 8 ]. In recent years, increased funding and research focus has shifted to the development of point-of-care diagnostics that will detect the causative agents of neglected tropical diseases [ 6 ].…”
Section: Introductionmentioning
confidence: 99%